Are current syndicated loan alliances related to past alliances? - Champagne, Claudia; Kryzanowski, Lawrence (Journal of Banking & Finance, 2007)
The odds of a current syndicate relationship between two lenders depend upon their previous alliances. The odds are significantly higher [lower] and strongest for a current lead–participant relationship with a continuation [reversal] of their previous roles. To illustrate, the odds are nearly four times higher when two lenders have allied in the previous 5years. The strength of lead–participant syndicate relationships between two lenders with same-ordered roles is most sensitive to the lead bank’s reputation and informationally opaque participants tend to have stronger relationships with lead banks. Lenders exhibit home bias in their syndicate alliances since ongoing relationships are stronger with domestic counterparts.